2019
DOI: 10.1080/17429145.2019.1603405
|View full text |Cite
|
Sign up to set email alerts
|

Increased CO2concentrations increasing water use efficiency and improvement PSII function of mulberry seedling leaves under drought stress

Abstract: Tang & Baiyi An (2019) Increased CO 2 concentrations increasing water use efficiency and improvement PSII function of mulberry seedling leaves under drought stress,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 76 publications
4
19
1
1
Order By: Relevance
“…Positive values of L-band suggested a lower energetic connectivity and poor stability of the system in seven genotypes at anthesis that could be the consequence of mild drought stress. It has been shown that drought stress causes changes in PSII photochemistry, which could be connected to reorganisation and stability reduction of thylakoid membranes by declining the levels of PSII proteins, especially those in PSII antennae (Chen et al 2016, Liu et al 2019 directly affecting connectivity and stability of PSII.…”
Section: Discussionmentioning
confidence: 99%
“…Positive values of L-band suggested a lower energetic connectivity and poor stability of the system in seven genotypes at anthesis that could be the consequence of mild drought stress. It has been shown that drought stress causes changes in PSII photochemistry, which could be connected to reorganisation and stability reduction of thylakoid membranes by declining the levels of PSII proteins, especially those in PSII antennae (Chen et al 2016, Liu et al 2019 directly affecting connectivity and stability of PSII.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the effects of eCO 2 varied from plant species to species. As a substrate for plant photosynthesis, eCO 2 certainly affects the CO 2 assimilation processes by increasing intercellular CO 2 and carboxylation efficiency of Rubisco while reducing stomatal conductance and photorespiration ( Sekhar et al, 2014 , 2015 ; Li et al, 2017 ; Liu et al, 2019 ), leading to an accumulation of soluble sugar and starch. Interestingly, significant differences in the accumulation of carbohydrates were found in mulberry grown under altered daytime vs. nighttime, and continuous eCO 2 treatment ( Figures 5F,G ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, all abovementioned increases were higher under S13 than under K2 ( Sekhar et al, 2015 ). Recently, 800 μmol mol –1 eCO 2 alleviated drought stresses on 1 year “Qinglong” mulberry seedlings by increasing their leaf water use efficiency and PSII photochemical activity ( Liu et al, 2019 ). The number and biomass of inflorescence in female, not in male of the mulberry tree, were increased after 18 months eCO 2 (ambient plus 380 μmol mol –1 CO 2 exposure) ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit and salinity, which are considered more relevant within a 30-year time frame will have a stronger negative effect on the planet survival than the actual change in CO 2 atmospheric concentration [11]. Studies on the synergistic effect of high CO 2 concentration and moderate drought have shown positive effects of high CO 2 conditions on the drought tolerance of some C 3 and C 4 species [12,13]. However, according to some studies, C 3 plants are more competitive than C 4 species under these conditions [14,15], while according to others, the intensity of photosynthesis increases in C 4 plants [15,16] due to more efficient water usage [17].…”
Section: Introductionmentioning
confidence: 99%